Studies on Allelochemicals in Synedrella nodiflora and Impact of Its Leaf Leachates on Germination and Seedling Growth of Radish (Raphanus sativus) and Mustard (Brassica juncea) - Ghayal, N.A.; Dhumal, K.N.; Deshpande, N.R.; Shah, S.M.; Ruikar, A.D. (Asian Journal of Chemistry, 2010)
Synedrella nodiflora is the highly dominant obnoxious invasive alien weed species through out the campus of Pune University, India. Its leaf leachates stimulated the seed germination of mustard (Brassica juncea) and radish (Raphanus sativus) at low concentrations (2.5-5.0 %), but higher concentrations (15-20 %) were most inhibitory to both test plants. The higher concentrations were most inhibitory to seed germination and seedling growth. The phytochemical and TLC analyses revealed that Synedrella leaves were rich in phenolics and various neutral and non-polar compounds and allelochemicals like tannins and glycosides.